Astronomical Cardiology: A Search For Heartbeat Stars Using $Gaia$ and $TESS$ - Jowen Callahan; D. M. Rowan; C. S. Kochanek; K. Z. Stanek (The Open Journal of Astrophysics, 2025)
Heartbeat stars are a subclass of binary stars with short periods, high eccentricities, and phase-folded light curves that resemble an electrocardiogram. We start from the $Gaia$ catalogs of spectroscopic binaries and use $TESS$ photometry to identify 112 new heartbeat star systems. We fit their phase-folded light curves with an analytic model to measure their orbital periods, eccentricities, inclinations, and arguments of periastron. We then compare these orbital parameters to the $Gaia$ spectroscopic orbital solution. Our periods and eccentricities are consistent with the $Gaia$ solutions for 85$%$ of the single-line spectroscopic binaries but only 20$%$ of the double-line spectroscopic binaries. For the two double-line spectroscopic binary heartbeat stars with consistent orbits, we combine the $TESS$ phase-folded light curve and the $Gaia$ velocity semi-amplitudes to measure the stellar masses and radii with $PHOEBE$. In a statistical analysis of the HB population, we find that non-giant heartbeat stars have evolved off the main sequence and that their fractional abundance rises rapidly with effective temperature.